The Effectiveness of TU Health Check Up Program Model by Lean and Eliminate Combine Rearrange Simplify Concept - Saensuk, Nantana; Hansakunachai, Tippawan (Journal of The Royal Thai Army Nurses, 2022)
This research and development. Objectives 1.To develop a service process model 2. To compare the waiting times before and after using the service process model and 3.To increase satisfaction score on Check Up Program.The data were collected during March-June, 2020. (Excluding April 2020 the TU Health Check Up Center was closed due to COVID-19). Results comparing time using the old model which consists of 11 steps and improved model of 9 steps, we found that the time taking on choosing Check Up Program was reduced and contact the financial department was reduce and getting EKG was reduced. This model couldn’t reduce time in others process. In addition, improved process provides smoother and less complications for faster service and satisfaction level of .05